Continuation or change? Borders and frontiers in late antiquity and medieval Europe
1 online resource
Keywords: "This volume examines interdisciplinary boundaries, and includes texts focusing on material culture, philological analysis and historical research. What they all have in common are zones that lie in between, not treated as mere barriers, but also places of exchange in the early Middle Ages. Continuation or Change is a useful resource for upper-level undergraduates, postgraduates, and scholars interested in medieval warfare, Eastern European history, medieval border-regions and cross-cultural interaction"--